Agravos bucais em crianças e adolescentes com paralisia cerebral institucionalizadas na APAE de Campina Grande – PB - Cardoso, Andreia Medeiros Rodrigues (2014)
Evaluating the frequency and factors associated with oral diseases in pediatric populations with cerebral palsy is necessary for the planning and implementation of health promotion programs. The aim of this study was to determine the prevalence and factors associated with dental caries, periodontal changes and dental trauma in children and adolescents with cerebral palsy. A cross-sectional study was carried out with a non- probabilistic sample of 80 patients aged 2-18 years treated in a rehabilitative institution in northeastern Brazil. Clinical data were obtained from medical records, while caregivers answered a socioeconomic questionnaire. Oral examinations were performed by calibrated investigator (K = 0,66-1,00), with record of DMFT, dmft, Gingival Bleeding Index (GBI), Community Periodontal Index (CPI), Dental Aesthetic Index, malocclusion and Dental Trauma. Possible Associations were verified by bivariate and multivariate Poisson regression analysis (α = 0,05). The results revealed prevalence of dental caries of 59,3%, with average DMFT and dmft of 1,71+2,42 and 2,22+3,23, respectively. In periodontal evaluation, 89,9% showed changes. The average GBI was 22,44% and the prevalence of gingival bleeding, calculus, shallow and deep periodontal pockets, were 94,73%, 79,62%, 12,90% and 3,22%, respectively. The prevalence of dental trauma was 36,3%, with enamel fracture being the most common dental trauma (89,1%). In multivariate analyses, schooling of less than eight years of caregiver (OR = 1,43; 95% CI = 1,09-1,89) was associated with caries experience. Periodontal changes were associated with female gender (OR = 0,82; 95% CI = 0,69-0,97), schooling less than eight years of caregiver (OR = 1,15; 95% CI = 1,03-1,29), poor oral perception (OR = 0,89; 95 CI% = 0,80-0,98), severe communication impairment (OR = 0,87; 95% CI = 0,76-0,99) and athedoid CP (OR = 0,85; 95% CI = 0,75-0,97). However, dental trauma was not associated with socioeconomic, oral and systemic characteristics (p> 0,05). It was concluded that individuals with CP showed high prevalence of dental caries, periodontal changes and dental trauma and except for dental trauma, associations with socioeconomic and systemic characteristics.